The Frequency and Risk Factors of Diabetic Foot Ulcer Recurrence Among Jordanian Patients with Diabetes - Tabanjeh, Sinan F.; Hyassat, Dana; Jaddou, Hashem; Younes, Nidal A.; Robert, Asirvatham A.; Ajlouni, Kamel (Current Diabetes Reviews, 2020)
Background: Diabetic foot is a major public health problem and their complications are an imperative cause of morbidity and mortality in diabetes. Objective: To evaluate the rate of recurrence of foot ulcers post two years of follow-up, including the associated risk factors in the patients attending the diabetic foot clinic at the National Center for Diabetes, Endocrinology, and Genetics (NCDEG), Amman, Jordan. Methods: A historical cohort design was adopted for the patients who presented for the first time to the diabetic foot clinic at the NCDEG. Every patient who came to the clinic was reviewed by using his or her medical files with respect to diabetic foot-related complaints. Patients were classified under four categories: (1) Recurrent foot ulcers (2) chronic foot ulcer (3) free of recurrence, and (4) no foot ulcers. Among the four groups, group 1 (recurrent foot ulcers, n=76) and group 3 (free of recurrence, n=54) were included for the analysis. Results: Among the 141 patients who presented to the diabetic foot clinic during the two-year study period, 76 (53.9%) of them experienced ulcer recurrences, 54 (38.3%) were recurrence-free, and 11 (7.8%) had chronic ulceration. The two-year recurrence rate was 58.5%. The presence of deformity and osteomyelitis were the statistically significant independent risk factors for recurrent foot ulceration. Conclusion: This study of recurrences was clearly related to the type and complications of the ulcers rather than to the other variables. Recurrent foot ulceration is linked to the presence of osteomyelitis and/or deformities.
Keywords: diabetic foot